Effect of Locally Processed Cassava (Manihot Esculenta) Root Meal on Performance Indices, Metric Characteristics of Gut and Organs of Broiler - Olatundun, Bukola Ezekiel (Universitas Andalas, 2023)
A 4-week feeding trial was conducted with 54 two-week-old broiler chicks which were randomly allotted to 3 dietary treatments, each treatment having 6 replicates consisting of 3 broilers in a completely randomized design to evaluate the influence of inclusion in broiler diets at 0, 7.5 and 12.5 % cassava root meal on feed intake, weight gain, feed conversion efficiency, organ weight and gut morphometry. Results showed that there was no significant difference (p>0.05) in the feed intake, weight gain and feed conversion efficiency among the treatments. There was also no significant (p>0.05) difference in the absolute weight of organs selected for analysis while there was a significant (p<0.05) difference in the right caeca length. Sun-dried cassava root meal can be incorporated into the starter diet of broilers up to 12.5% to replace conventional feed ingredients like maize without any deleterious effects on the performance and gut health.